2021
DOI: 10.1002/acn3.51318
|View full text |Cite
|
Sign up to set email alerts
|

Responsive neurostimulation for focal motor status epilepticus

Abstract: No clear evidence-based treatment paradigm currently exists for refractory and super-refractory status epilepticus, which can result in significant mortality and morbidity. While patients are typically treated with antiepileptic drugs and anesthetics, neurosurgical neuromodulation techniques can also be considered. We present a novel case in which responsive neurostimulation was used to effectively treat a patient who had developed super-refractory status epilepticus, later consistent with epilepsia partialis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Similar results were obtained from a review of eight patients implanted with DBS targeting the zona incerta, anterior thalamic nucleus or centromedian thalamic nucleus [64]. Other recent single case reports show efficacy for status epilepticus treatment, including 6 Hz DBS of the bilateral centromedian nucleus [43], RNS with two occipital strips [65] and TMS for occipital-onset seizures [47].…”
Section: Stimulation For Status Epilepticussupporting
confidence: 79%
“…Similar results were obtained from a review of eight patients implanted with DBS targeting the zona incerta, anterior thalamic nucleus or centromedian thalamic nucleus [64]. Other recent single case reports show efficacy for status epilepticus treatment, including 6 Hz DBS of the bilateral centromedian nucleus [43], RNS with two occipital strips [65] and TMS for occipital-onset seizures [47].…”
Section: Stimulation For Status Epilepticussupporting
confidence: 79%
“…Of the 81 studies in the literature that met the inclusion criteria, 13–92 the majority (60) reported only one patient. The remaining studies characterized a variable number of patients, ranging from 2 to 20.…”
Section: Resultsmentioning
confidence: 99%
“…These are connected to a programmable device which is cranially implanted and can provide electrical stimulation in response to detected ictal electrocorticographic activity [46]. About 10 cases have been described and the results are positive [47][48][49][50], and likely more cases will be described soon, but the published peer-reviewed cases regard adults and thus further details were considered out of scope of this review for the paediatric population.…”
Section: Invasive Neuromodulation Techniquesmentioning
confidence: 99%